A new strategy for CO2 utilization with waste plastics: conversion of hydrogen carbonate into formate using polyvinyl chloride in water. Issue 2 (4th November 2019) - Lu, Lihui; Zhong, Heng; Wang, Tianfu; Wu, Jianeng; Jin, Fangming; Yoshioka, Toshiaki
Abstract : A new and green approach for hydrogen carbonate reduction and PVC dechlorination in water in a single step. Abstract : This work reports the first observation of the reduction of hydrogen carbonate to formate with polyvinyl chloride (PVC) as a hydrogen source in high-temperature water. Results show that NaHCO3 is successfully converted into formate with a 16% yield and nearly 100% selectivity based on hydrogen carbonate, simultaneously achieving the complete dechlorination of PVC at 300 °C. The mechanistic study suggests that CH–OH group formation from the substitution reaction of chlorine in PVC by OH − is an important starting step, and then the CH–OH group and HCO3 − react to form formate via a redox reaction. Moreover, the selection of water as the reaction medium played a key role in the reduction of HCO3 − to formate using PVC. The present study provides a new and green method for not only hydrogen carbonate/CO2 conversion but also PVC waste dechlorination in a single step.